pDC Activation by TLR7/8 Ligand CL097 Compared to TLR7 Ligand IMQ or TLR9 Ligand CpG - Jing Wu; Shuang Li; Tete Li; Xinping Lv; Mingyou Zhang; Guoxia Zang; Chong Qi; Yong-Jun Liu; Liang Xu; Jingtao Chen (Journal of Immunology Research, 2019)
Plasmacytoid dendritic cells (pDCs) express high levels of the toll-like receptors (TLRs) TLR7 and TLR9. In response to TLR7 and TLR9 ligands, pDCs are primary producers of type I interferons. Our previous study demonstrated that pDCs activated by the TLR7 ligand imiquimod (IMQ) and the TLR9 ligand CpG A can kill breast cancer cells in vitro and inhibit tumor growth in vivo. Moreover, we observed a distinctive morphological, phenotypic change in pDCs after activation by IMQ and CpG A. However, the effect of other TLR7 and TLR9 ligands on pDCs remains less understood. In this study, we treat pDCs with the TLR7 ligand IMQ, TLR7/8 ligands (CL097 and CL075), and three TLR9 ligands (different types of CpGs). The size of pDCs increased significantly after activation by TLR7, or TLR7/8 ligands. TLR7, TLR7/8, and TLR9 ligands similarly modulated cytokine release, as well as protein expression of pDC markers, costimulatory molecules, and cytotoxic molecules. Interestingly, TLR7/8 ligands, especially CL097, induced stronger responses. These results are relevant to the further study of the role and mechanism of pDC-induced antitumor effects and may aid in the development of a new strategy for future tumor immunotherapy.